Pengembangan Model Penerimaan Teknologi Termodifikasi Pada Persepsi Jarak Sosial, dan Persepsi Jarak fisik - Agus Pamuji (APIC, 2020)
Technology acceptance models continue to change with modifications. In this study, two new aspects will be included, namely social distance and physical distance as factors that can influence the acceptance and use of information technology, especially using social media. These two factors are considered essential. Besides that, in essence, these two factors are still under the social influence that has been widely studied. However, if social influence tends to have a subjective element so that it is related to subjective norms, then the perception of social distance and physical distance is an influence from the environment in addition to subjective norms. This study uses theoretical study methods and tracing various sources that will be included and produce new models. Thus, the perception of social distance and the perception of physical distance become a modified TAM model.